Pengaruh Brand Ambassador Park Hyung Sik Terhadap Brand Image Avoskin - Nursafitri, Nilam; Putri, Berlian Primadani Satria (Universitas Batanghari Jambi, 2024)
This study aims to determine and analyze whether there is influence and how much brand ambassador Park Hyung Sik has on Avoskin's brand image. Data collection in this study was carried out using quantitative methods including descriptive analysis, regression test, coefficient of determination, hypothesis, and validity and reliability. This research was conducted using a quantitative type method, with descriptive and associative properties because it is able to provide an explanation regarding the relationship between the two variables, namely brand ambassadors to brand image. In this study, the technique used in data collection used a survey method by distributing questionnaires via Google Form. The results in this study showed a positive influence on Brand Ambassador Park Hyung Sik (X) on Brand Image Avoskin (Y), with simple linear regression results with a value of 1.420. Therefore, when the value increases by 1%, the Brand Ambassador will increase by 1.420 and the Brand Image variable will also increase by 6258.905. This proves that the value of the Brand Ambassador has grown, so the Brand Image has also increased. The research was conducted using the Viscap model.